Epidemiological Profile of Cleft Lip and Palate Cases in A Libyan Neonatal Unit at Al Wahda Teaching Hospital, Derna: A Comprehensive Analysis - Algadhy, Ranya; Bojazyah, Aisha (Khalij-Libya Journal of Dental and Medical Research, 2024)
Aim. This study aims to assess the prevalence and associated risk factors of Cleft lip and palate (CLP) among neonates in Derna, Libya, over a six-year period from 2016 to 2021. Methods. This retrospective observational study analysed data from the neonatal unit registry at Al Wahda teaching hospital in Derna, Libya. The study population comprised neonates admitted to the hospital from 2016 to 2021. Inclusion criteria specified Libyan neonates diagnosed with CLP, while exclusion criteria excluded stillbirths and non-Libyan neonates. Data analysis involved calculating incidence rates, descriptive statistics, and subgroup analyses to identify demographic characteristics and associated risk factors. Results. Out of 2,887 neonatal records reviewed, 10 cases of cleft lip ± palate (CL±P) were identified, yielding an overall incidence rate of 0.6 cases per 1000 live births. The majority of cases (50%) presented with both cleft lip and palate, followed by cleft palate only (40%) and cleft lip only (10%). Demographic analysis revealed a higher prevalence among females (60%), full-term neonates (80%), neonates from larger families of more than 6 children (50%), and those with birth weights between 2.5 and 4 kg (70%). Left-sided clefts were more common (90%) than right-sided clefts (10%). Potential risk factors included maternal history of abortion (20%), irregular pregnancy follow-up (90%), and gestational diabetes (10%). Conclusion. This study provides insights into the prevalence and associated risk factors of cleft lip ± palate (CL±P) among neonates in Derna, Libya. The findings underscore the importance of comprehensive prenatal care and public health interventions to address modifiable risk factors and reduce the incidence of cleft lip ± palate in affected populations. Further research is needed to explore additional factors contributing to cleft anomaly occurrence and outcomes. الأهداف. تهدف هذه الدراسة إلى تقييم مدى انتشار الشفة المشقوقة والحنك المشقوق وعوامل الخطر المرتبطة به بين حديثي الولادة في درنة، ليبيا، على مدى ست سنوات من 2016 إلى 2021. طرق الدراسة. قامت هذه الدراسة الرصدية الاسترجاعية بتحليل البيانات من سجل وحدة حديثي الولادة في مستشفى الوحدة التعليمي في درنة، ليبيا. تألف مجتمع الدراسة من حديثي الولادة الذين تم إدخالهم إلى المستشفى من عام 2016 إلى عام 2021. حددت معايير الشمول حديثي الولادة الليبيين الذين تم تشخيص إصابتهم بـ CLP، في حين استبعدت معايير الاستبعاد حالات الإملاص والولدان غير الليبيين. وشمل تحليل البيانات حساب معدلات الإصابة، والإحصاءات الوصفية، وتحليلات المجموعات الفرعية لتحديد الخصائص الديموغرافية وعوامل الخطر المرتبطة بها. النتائج. من بين 2887 سجلاً لحديثي الولادة تمت مراجعتها، تم تحديد 10 حالات من الشفة المشقوقة (CL±P)، مما أدى إلى معدل حدوث إجمالي قدره 0.6 حالة لكل 1000 ولادة حية. غالبية الحالات (50%) تعاني من الشفة المشقوقة والحنك المشقوق، يليها الحنك المشقوق فقط (40%) والشفة المشقوقة فقط (10%). كشف التحليل الديموغرافي عن ارتفاع معدل الانتشار بين الإناث (60%)، وحديثي الولادة مكتملي النمو (80%)، وحديثي الولادة من أسر أكبر تضم أكثر من 6 أطفال (50%)، وأولئك الذين تتراوح أوزانهم عند الولادة بين 2.5 و4 كجم (70%). كانت الشقوق في الجانب الأيسر أكثر شيوعًا (90٪) من الشقوق في الجانب الأيمن (10٪). وتشمل عوامل الخطر المحتملة تاريخ الأم للإجهاض (20٪)، ومتابعة الحمل غير المنتظمة (90٪)، وسكري الحمل (10٪). الخاتمة. تقدم هذه الدراسة نظرة ثاقبة حول مدى انتشار وعوامل الخطر المرتبطة بالشفة المشقوقة والحنك المشقوق (CL±P) بين الولدان في درنة، ليبيا. تؤكد النتائج على أهمية الرعاية الشاملة قبل الولادة وتدخلات الصحة العامة لمعالجة عوامل الخطر القابلة للتعديل وتقليل حدوث الشفة المشقوقة والحنك المشقوق في السكان المتضررين. هناك حاجة إلى مزيد من البحث لاستكشاف العوامل الإضافية التي تساهم في حدوث الشذوذ المشقوق ونتائجه.